2010
DOI: 10.1042/bsr20100018
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cancer spheres are more than just aggregates of stem marker-positive cells

Abstract: SynopsisPancreatic cancer stem-like cells are described by membrane expression of CD24, CD44 and ESA (epithelial-specific antigen) and their capacity to grow as spheres in a serum-free medium containing well-defined growth factors. The capacity of a panel of four pancreatic cancer cell lines (PANC-1, CFPAC-1, PancTu-1 and PSN-1) to form spheres was tested. All cell lines with the exception of PancTu-1 developed spheres. Phenotypically, the sphere-growing cells showed an increased in vitro invasion capability. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 27 publications
6
78
0
2
Order By: Relevance
“…In study of Gavirhi et al, Panc1 cells also aggregated to form spheres in serum-free DMEM/F-12 containing B27, fungizone, heparin, EGF and FGF, and the sphere cells showed stem cell functionalities. 8 This result is similar to ours. How the pancreatic cancer cells acquired CSC characteristics in the serum-free DMEM/F-12 medium containing EGF, bFGF, B27 and insulin?…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In study of Gavirhi et al, Panc1 cells also aggregated to form spheres in serum-free DMEM/F-12 containing B27, fungizone, heparin, EGF and FGF, and the sphere cells showed stem cell functionalities. 8 This result is similar to ours. How the pancreatic cancer cells acquired CSC characteristics in the serum-free DMEM/F-12 medium containing EGF, bFGF, B27 and insulin?…”
Section: Discussionsupporting
confidence: 82%
“…7 Gavirhi et al showed that Panc1 cells aggregated to form spheres in serum-free Dulbecco's modified Eagle medium/ Nutrient Mixture F-12(DMEM/F-12) containing B27, fungizone, heparin, fibroblast growth factor(FGF) and epidermal growth factor(EGF), and the sphere cells showed increased tumor-initiating ability and aggressiveness, which are CSC characteristics. 8 Although the characteristics of CSCs have been studied extensively in recent years, there is still some debate about the CSC hypothesis and the origin of CSCs is still uncertain. Tumor heterogeneity has been explained by 2 different models.…”
Section: Introductionmentioning
confidence: 99%
“…3D models such as tumor spheres or microtissue more closely mimic the tumor microenvironment than do monolayers of cancer cells. Previous groups have attempted diverse paraffinembedding techniques with several disadvantages, including difficulties in obtaining accurate sections of spheres due to agarose/clot embedding (47)(48)(49). When agarose/clot embedding of mammospheres is performed, mammospheres do not stay in a single plane but sink to different deep layers.…”
Section: Discussionmentioning
confidence: 99%
“…26 In pancreatic and colon cancer a high expression level of CD24 and CD44 characterizes cancer stem cells. [27][28][29] Figure 6 shows that the expression of CD24 and CD133 was significantly higher (P Ͻ 0.05), in DisNB than in the MetNB variants, whereas the c-kit expression was significantly lower (P Ͻ 0.01) in DisNB than in the MetNB variants. Both DisNB and MetNB cells did not express CD34 or CD44.…”
Section: Stem Cell Markersmentioning
confidence: 98%